Reinvención de la identidad étnica, nuevas territorialidades y redes globales: el Estado multiétnico y pluricultural en Colombia y Ecuador - Castillo, Luis Carlos; Cairo Carou, Heriberto (Sociedad y Economía, 2002)
The unitary State is undergoing change in several countries of Latin America. This change is associated with a crisis on three levels: legitimacy, participation, and representation. This paper studies, comparatively, how ethnic movements in Colombia and Ecuador, by means of a reinvention and strategic use of their identity, have challenged the mental image of the mestizo nation and have contributed to the recognition of ethnic and cultural diversity. It is argued that in this process the turn from a class-based policy to one attending to ethnic and cultural identity has been decisive.